Specifics of literary development in adolescence: The dynamism of socio-cultural transformations - Vladimir Sobkin; Dmitrij Plotkin (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The article bases on an opinion poll we made in April 2005 in several Moscow comprehensive schools, where our 2,510 respondents studied in the 7th, 9th, 10th and 11th grades. The probe continued a research cycle to monitor the dynamics of school students' changing artistic preferences, which we started in the mid-1970s. We discuss such conceptual aspects of literary development as information awareness in fiction, ability to adequately perceive the style of reading matter, and motivation of reading. Side by side with analyses of the impact of gender, age and social stratification, we pay special attention to changes in attitudes to fiction that took place in the teenager subculture within the preceding thirty years. Of greatest interest to us is analysis of the role of school studies in the formation of adolescents' interests in reading.